2017
DOI: 10.1007/s00894-017-3525-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth morphology of CL-20/HMX cocrystal explosive: insights from solvent behavior under different temperatures

Abstract: A 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (CL-20) /1,3,5,7-tetranitro-1,3,5,7-tetrazacyclooctane (HMX)-isopropanol (IPA) interfacial model was constructed to investigate the effect of temperature on cocrystal morphology. A constant volume and temperature molecular dynamics (NVT-MD) simulation was performed on the interfacial model at various temperatures (295-355 K, 20 K intervals). The surface electrostatic potential (ESP) of the CL-20/HMX cocrystal structure and IPA molecule were studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…It was observed that NH2, -COOH, and -OH (phenol) groups are exposed on most of the crystal facets. The exposed group may affect the polarities of the crystal facet, which then affects the interaction with the solvent [39][40]. The crystal facet with exposed oxygen atoms (high polarity) will contribute to the high electrostatic energy for the particular facets [53].…”
Section: Intermolecular Assessment Using Molecular Modelling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that NH2, -COOH, and -OH (phenol) groups are exposed on most of the crystal facets. The exposed group may affect the polarities of the crystal facet, which then affects the interaction with the solvent [39][40]. The crystal facet with exposed oxygen atoms (high polarity) will contribute to the high electrostatic energy for the particular facets [53].…”
Section: Intermolecular Assessment Using Molecular Modelling Techniquementioning
confidence: 99%
“…The molecular modeling simulation method is a widely used technique in crystal research [37], commonly used to predict crystal morphology and examine the growth mechanism at the atomistic/molecular level [38]. Validation of the predicted crystal morphology (commonly carried out in a vacuum environment) is a complex and challenging process in which in an actual situation, the crystals are grown in an environment with the presence of solvents and additives [39][40]. Molecular structure of a crystal is packed in a unit cell as a building unit and heavily depending on intermolecular interaction such as hydrogen bond and van der Waals between the molecules and are the important parameters, which affect the crystal shape, and hence the degree of solubility [41].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research on the morphology and phase purity showed that most solvents yield mixtures of phases of CL‐20, mainly the ε ‐form . The effects of solvents on the growth and morphology of CL‐20‐based cocrystals were also investigated, and the results indicated that the solvents have a cooperative effect in the cocrystallization. Moreover, the potential cocrystal formers of CL‐20 were studied through their molecular electrostatic potentials (MEPs) .…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6,8,10,12-Hexanitrohexaazaisowurtzitane, a polycyclic nitramine, commonly referred to as CL-20, is often found in these energetic-energetic co-crystals. CL-20 is currently the most powerful commercially available explosive, making it a major focus of cocrystallization efforts [1,[3][4][5][6][7][8][9][10][11][12][13][14][15]. CL-20 is of great interest for applications ranging from explosives to propellants; however, it is limited by its mechanical and thermal sensitivity to detonation [1,4,16].…”
Section: Introductionmentioning
confidence: 99%